ERP and EEG Markers of Brain Visual Attentional Processing - Zani, Alberto (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book comprises research articles contributed to the Special Issue on "ERP and EEG Markers of Brain Visual Attentional Processing" of the Brain Sciences journal by a panel of authoritative international cognitive neuroscientists and electrophysiologists. All articles present state-of-the-art knowledge on the relationships between visuospatial attentional processing and the brain in humans as investigated by means of EEG and ERPs from the perspective of cognitive neuroscience. All the articles compare overt behavioral data obtained in universally renowned visual selective attention protocols with the electrophysiological data obtained in these same protocols aimed at investigating different facets of visuospatial attentional processing. The research presented is interdisciplinary, ranging across visual selective processing mechanisms in health, the effects of psychological attentional dysfunctions and brain damage, and functional imaging of the human brain. The Preface of the book provides an overall theoretical introduction to the field and to the contents of each of the remaining articles. In this introductory Editorial, a framework is presented in which to consider EEG and ERPs as research tools able to contribute to both cognitive and brain sciences, putting together new knowledge about humans as integrated sociobiological individuals. This book may provide a useful starting point and reference for researchers and students of cognitive neuroscience, psychology, philosophy, or cognitive science who have an interest in mind and brain visual attentional processing.